Wisdom from the edge : writing ethnography in turbulent times - Stoller, Paul (Expertise (Ithaca, N.Y.), 2023)
"This book presents a blueprint for doing anthropology in troubled times. It instructs readers on how to convey important anthropological insights-indigenous wisdom-to a general audience in search of solutions to cotemporary social problems."--